The Impacts of Untreated Childhood Trauma Depicted in Dolores Redondo’s "The Invisible Guardian" - Nabila Shafa Salsabila (Journal of Translation, Linguistics and Literature, 2024)
Growing up, sometimes parent(s) unconsciously inflict trauma to their child, but in some cases, the parent(s) intentionally inflict harm to their child. As the child grow older, the impact of these traumatic events did not disappear easily from the survivor’s life. This study analyzes the impact left by traumatic childhood in adult life of Amaia Salazar, a Homicide Inspector who was obliged to go back to her hometown, and a place where this traumatic childhood took place in her childhood. This study uses psychological approach to literature as the main theoretical framework. Result from this study display some of the impact left by Amaia’s traumatizing childhood. Amaia is shown to have insomnia and frequent nightmares, problem with her maternal instinct and womanhood, and flashback and re-traumatization. All of these are combined impact of a traumatic childhood.